An Approach to the Research Methodology for a Doctoral Study (Journal of Governance and Development (JGD), 2023)
This paper discusses the research methodology employed in a doctoral studyentitled, “Impacts of legislative controls on private hospitals in Malaysia”.The research methodology encompasses the general design to the researchprocess, from the theoretical framework to the collection and the analysisof data. The paper commences with the discussion on the methodologicalapproaches as to whether a positivist or naturalistic framework or acombination of mixed method approach is most appropriate to be utilised inthis study. This methodological decision making process led to the choice of aqualitative study. It then describes the methods for data collection, the analysisand the coding process from the key informants’ interviews, observationsand discourses which formed the core of the research methodology. Severalemergent themes which are interlinked have been identified and crystallizedas the empirical findings that provide answers to the research questions andobjectives of the study.